CHEMICAL CRITERIA FOR ASSESSING THE ECOLOGICAL STATUS OF WATER BODIES - Shkumbatiuk Р.; Shkumbatiuk О.; Ivankiv М.; Hermanovych О.; Lopotych Н. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The article examines the chemical criteria for assessing the ecological conditions of water bodies, which is an important aspect of monitoring and protecting water resources. The main indicators of water quality, such as the level of pollutants, concentration of heavy metals, pH, dissolved oxygen content, and biochemical oxygen demand (BOD), are analyzed. Special attention is paid to analytical chemistry methods used to measure these indicators. The study's results highlight the necessity of a comprehensive approach to assessing the ecological state of water bodies, which includes both chemical analysis and consideration of other factors, such as physicochemical properties and biological criteria. The authors conducted a comprehensive analysis of the physicochemical parameters of water bodies and examined the mechanisms of heavy metals accumulation in bottom sediments. Three main mechanisms are described: adsorption on minerals, sedimentation of insoluble forms, and bioabsorption by aquatic organisms. The study's findings confirm that bottom sediments act as significant accumulators of toxins, which can influence water quality and overall ecosystem health. The relationship between soil enzyme activity (invertase and dehydrogenase) and soil contamination with heavy metals is explored. Notably, dehydrogenase activity is identified as a reliable bioindicator of heavy metal presence in soils, while invertase activity depends on humus content. The study concludes that increased anthropogenic burden leads to decreased enzyme activity and degradation of soil and aquatic ecosystems. The results provide valuable insights into the effects of heavy metals on water bodies and underscore the importance of chemical criteria in assessing the ecological conditions of water bodies. The authors give recommendations as to utilizing the findings to develop ecological standards and assess contamination risks.